Pengaruh Karakteristik Individu dan Faktor Psikologis Terhadap Keputusan Pembelian Konsumen pada Produk Blackberry - Sujana Sujana; Cindy Ekaputi Sim (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2012)
Cellular telephone as a communication tool that is easy to use and attractive is more and more widely circulated among the people. Consumers have many alternatives in determining the type of phone that will be used. In that case, comsumers’ behaviour plays an important role because purchasing decision depends on it. Consumers may respond to the effect which changes their mind in determining purchasing decision in the last minutes. Consumers’ behaviour is influenced by cultural factors, personal factors (individual characteristics), and psychological factors. Most of them are the factors which can not be controlled, but marketers must be taken into account. This research is a study about the factors influencing consumers’ purchasing decision on Blachberry products, those are individual characteristics and psychological factors. This research aims to find out the influence of individual characteristics to consumers’ purchasing decision on Blackberry products, to examine the influence of psychological factors to consumers’ purchasing decision on Blackberry products, to know the influence of individual characteristics and psychological factors to consumers’ purchasing decision on Blackberry products, and to determine the dominant factors affecting between individual characteristics and psychological factors. To answer the purpose of this study, it’s used multiple linear regression test, including simultaneous partial test and classic assumtion test. Sampling was done by using Slovin technique to as many as 100 respondents. The results show that both of the independent variables simultaneously have partial positive and significant influence onBlackberry purchasing decision. Lifestyle factors have positif, significant, and dominant effect towards purchasing decision. This can occur due to a shift in the use of Blackberry which was originally intended for business but currently shiftng toward lifestyle. Adjusted to R-square value of 0,458 or 45,8%, this figure shows that the individual characterstic variable (X1) and psichological factors (X2) contribute to the purchasing decision on Blackberry Cellular Phones. The rest affected by other factors is not examined. Based on classic assumtion test, it indicates that Ho is received, that means the residual data are normally distributed, with the result that it meet normality assumtion